The comparison between brachial artery reactivity using ultrasound on noncoronary artery disease and coronary artery disease in male patients - Mahmud, Zalina (2013)
Comparison between brachial artery reactivity using ultrasound in non-coronary artery disease and coronary artery disease male patients. Coronary artery disease (CAD) occurs due to coronary artery stenosis secondary to atherosclerosis. It is the most common cause of death worldwide. First clinical manifestations of cardiovascular disease often arise in a stage of well-advanced atherosclerosis. According to previous studies, measurement of peripheral vascular function can accurately exclude CAD in subjects undergoing non invasive assessment for atherosclerosis. Degree of brachial artery dilatation following forearm occlusion by ultrasound are now commonly used in clinical studies as a measure of endothelial function of coronary artery. Thus, degree of brachial artery dilatation can provide a “window” to coronary artery disease. 1- To determine measurement of brachial artery pre and post exercise in CAD and non-CAD candidates 2- To determine degree of dilatation in both CAD and non-CAD groups of candidates 3- To compare dilatation measurement of brachial artery between non-CAD and CAD candidates. High resolution ultrasound examination of right brachial artery was performed on 43 candidates which was 26 non-CAD candidates and 17 established CAD candidates. Brachial artery measurement pre and post exercise following occlusion were measured in two different sites namely at 2 cm and 10 cm for each candidate. At these sites, 3 dimension of measurements taken namely anteroposterior (AP), width (W) and craniocaudal (CC). Brachial artery dilatation was significantly higher in non-CAD candidates as compared to CAD candidate (12.5% to 14% vs 9% to 11%). There was also significant differences in mean measurement of brachial artery between pre and post exercise in non-CAD and non-CAD group of candidates with p-value<0.05. Range of measurements before exercise for non-CAD candidates was 0.38 cm to 0.65 cm while in CAD group range of measurement was 0.35 cm to 0.57 cm. Range of measurements post exercise for non-CAD was 0.43 cm to 0.75 cm while in CAD range was from 0.37 cm to 0.70 cm. Mean pre exercise measurements in non-CAD candidates were 0.50 cm and 0.53 cm while in CAD candidates, measurements were 0.49 cm and 0.44 cm for two different locations. For post mean exercise measurements, measurements were 0.57 cm/ 0.59 cm for non-CAD and 0.56 cm /0.48 cm for CAD candidates. Results of this study demonstrate significant relationship between degree of brachial artery dilatation in prediction of patients with or without CAD. High resolution ultrasound of brachial artery can be used as a screening tool for early detection of CAD before symptoms occurs.